2008
DOI: 10.1175/2007mwr2116.1
|View full text |Cite
|
Sign up to set email alerts
|

Generalized VTD Retrieval of Atmospheric Vortex Kinematic Structure. Part I: Formulation and Error Analysis

Abstract: The primary circulation of atmospheric vortices, such as tropical cyclones and tornadoes, can be estimated from single-Doppler radar observations using the ground-based velocity track display (GBVTD) algorithm. The GBVTD algorithm has limitations in the following four areas: 1) distortion in the retrieved asymmetric wind fields, 2) a limited analysis domain, 3) the inability to resolve the cross-beam component of the mean wind, and 4) the inability to separate the asymmetric tangential and radial winds. This p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(33 citation statements)
references
References 16 publications
0
33
0
Order By: Relevance
“…Note V M is a function of altitude only. Interested readers can find the definitions of variables in LJCD, their appendix A. ApproximatingV d /cosf with V d as in Jou et al (2008), the azimuthal gradient of V d can be obtained by taking the derivative of (3) with respect to azimuth relative to vortex center (referred to as azimuth):…”
Section: The Grvtd Technique a Mathematical Formulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Note V M is a function of altitude only. Interested readers can find the definitions of variables in LJCD, their appendix A. ApproximatingV d /cosf with V d as in Jou et al (2008), the azimuthal gradient of V d can be obtained by taking the derivative of (3) with respect to azimuth relative to vortex center (referred to as azimuth):…”
Section: The Grvtd Technique a Mathematical Formulationmentioning
confidence: 99%
“…A series of VTD extensions (referred to as the ''VTD family of techniques'')-including extended VTD (EVTD; Roux and Marks 1996), the ground-based VTD (GBVTD; Lee et al 1999, hereafter LJCD), ground-based extended VTD (GB-EVTD; Roux et al 2004), extended GBVTD (EGBVTD; Liou et al 2006), and generalized VTD (GVTD; Jou et al 2008)-expanded the VTD analysis into multiple flight legs for airborne Doppler radar and multiple ground-based Doppler radars (e.g., Roux and Marks 1996;Lee et al 2000;Harasti et al 2004;Liou et al 2006; Lee and Bell 2007;Zhao et al 2008). Recently, the GBVTD technique has been incorporated into the Vortex Objective Radar Tracking and Circulation (VORTRAC) software for real-time analysis of TCs at the National Hurricane Center (NHC) of the United States.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, since the Nyquist velocities used by operational weather radars are usually in the range between 20 and 30 m s 21 , radial velocities scanned from intense atmospheric vortices can easily exceed these Nyquist velocities and become severely aliased. Thus, radar velocities had to be dealiased first before they were applied to the aforementioned vortex models and other complex vortex models (Lee et al 1999;Liou et al 2006;Jou et al 2008). Because of this and the reason explained below, it is desirable and useful to develop an alias-robust method that can estimate the vortex intensity and gross structure by directly fitting a parametric vortex model to raw aliased velocity data.…”
Section: Introductionmentioning
confidence: 99%
“…While manipulating the Doppler velocity equation to formulate the generalized VTD (GVTD) technique, Jou et al (2008) showed that the atmospheric vortex signatures displayed in rV d (V d scaled by the distance from the radar to the gate, r) had several advantages over those displayed in V d and simplified the governing equations. First, the signature of a constant wind (Fig.…”
Section: Introductionmentioning
confidence: 99%